2021
DOI: 10.1088/1755-1315/759/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of peanut shell waste and bio-slurry as organic fertilizer for sweet corn (Zea mays L. Saccharata)

Abstract: The increasing demand for sweet corn (Zea mays, L.) in order to meet community nutrition has encouraged farmers to make improvements to the cultivation system. One of the important factors in the process of increasing sweet corn production is soil nutrients. Peanut shell (Arachys hypogea. L.) and bio-slurry are organic waste, when they have undergone a decomposition process they can be used as organic fertilizers. The aim of the study was to test the correct dosage of peanut shells and the concentration of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This is because both of them provide nutrients that are essential to plant growth. Several findings from previous studies substantiate the same: Application of bio-slurry provides both macro (N, P, K) and micronutrients (Zn, Mn, B) and increase growth and yield variables of field crops, including maize [ [10] , [11] , [12] , [13] ]. Maize agronomic performances increased with increasing rate of bio-slurry [ 10 ].…”
Section: Discussionmentioning
confidence: 64%
“…This is because both of them provide nutrients that are essential to plant growth. Several findings from previous studies substantiate the same: Application of bio-slurry provides both macro (N, P, K) and micronutrients (Zn, Mn, B) and increase growth and yield variables of field crops, including maize [ [10] , [11] , [12] , [13] ]. Maize agronomic performances increased with increasing rate of bio-slurry [ 10 ].…”
Section: Discussionmentioning
confidence: 64%
“…The findings of this study were consistent with previous results. Roeswitawati et al (2021) found that peanut bran and biological mud had significant effects on the growth and yield of sweet corn, with 15 tons/ha of peanut bran and 125 ml/L of biological mud having the best effect. The average price of flue-cured tobacco was the highest after the mixed application of cow manure and rapeseed oil meal, which indicated that rapeseed oil meal could improve the quality of flue-cured tobacco.…”
Section: Discussionmentioning
confidence: 99%